Literatura de cordel e interdisciplinaridade: rumos da literatura popular no Tocantins - Santos, Arisvaldo da Silva (2018)
This research mainly holds up in analyzes about how the popular literature of teaching / Cordel literature is discussed in mainstream education documents. The type of research was the literature and documents, through a qualitative methodology, which first studied the popular literature and its relation to orality subsequently researched the emergence of string literature in Brazil, in a third time we analyze the that link the official documents governing the Portuguese language teaching and literature. Finally, we look at some research that dialogue with the literature of Cordel and teaching different subjects, pointing thus a way to interdisciplinarity. Although far from school curricula Portuguese language, Cordel literature is present in dialogues with other areas of knowledge in education. Are not unknown large amounts of research carried out in education using as a basis works of popular Cordel poets in the teaching of mathematics, physics, history, education, geography and others. This not only shows their relevance for teaching as well as their ability to talk across disciplines. The string literature has used different topics today addressing issues such as gender, homosexuality, education, politics and others, demonstrating its wide capacity to operationalize debates in several other fields in addition to the literature. The string literature is a culture asset that viscejou especially in northeastern Brazil and is gradually getting value which over the centuries was denied. Initially it was considered only a culture connected to the folklore of the region, with time, from various studies in higher education institutions, it became known and began to be seen as more a literary aspect of popular origin. That was enough for the LC to become known and gain the value that has been denied over time. This research has the objective to develop studies that emphasize the issues raised above, taking the LC object in synchronic terms, from its location in a specific area of Brazil and diachronic, from its development throughout history. Therefore, we will use the findings collected in studies with teacher Valéria Medeiros.